A Bibliometric Analysis of Research on the Mental Health of Gifted and Talented Children (1948-2025) - Dagli , Namrata; Dagli , Rushabh; Haque , Mainul (Bangladesh Journal of Medical Science, 2025)
This study offers a comprehensive overview of global research on the mental health of gifted and talented children, conducted through a bibliometric analysis of articles published between 1948 and 2025. Using the Dimensions database, 114 relevant peer-reviewed articles were identified and analyzed to map trends in citation, publication, and thematic focus. In addition, the citation network of influential countries, sources, and articles in the field was analyzed using VOSviewer and Biblioshiny. The results show that research on this topic has steadily increased since the late 1990s, particularly after 2017, with a growing interest in issues such as ADHD, socioemotional development, the impact of parenting style, sleep, and specialized education. The findings suggest that the concept of giftedness has evolved from a focus on cognitive performance to a more holistic view, one that is more focused on the emotional and psychological needs of gifted children. This analysis offers valuable insights for researchers, educators, and mental health professionals seeking to support gifted children. BJMS, Vol. 24 No. 03 July’25 Page : 764-777